Management of infantile hemangiomas: Recent advances - Xu, Wei; Zhao, Haiguang (Frontiers in Oncology, 2022)
Infantile hemangiomas (IHs) are benign vascular tumors commonly observed in children. A small number of cases can manifest as organ or system dysfunction, permanent scarring, or even disfigurement. Currently, diagnosis is mainly based on clinical history, physical examination, and auxiliary inspection. In the treatment of a hemangioma, the functional damage caused by the lesion and complications that may endanger the patient’s life should be given priority. This suggests that identification, diagnosis, and referral to specialists during the early stages of IHs are important factors in preventing related complications and obtaining a better prognosis. During the past few decades, researchers have explored different treatments according to the condition, including oral or topical drugs, topical drug injections, laser surgery, and surgical treatment. However, oral propranolol remains a well-accepted first-line treatment. This article will primarily focus on the recent advances in the clinical diagnosis and treatment of hemangiomas, along with a literature review on the subject.